Family fiqh in Malaysia :an analysis of the selected issues - Haneef, Sayed Sikandar Shah (Islamic Book Trust, 2021)
The discourse on family fiqh in Malaysia within the broader national agenda of “strengthening Islamic family values” to maintain its indigenous Islamic characteristics in the age of globalization is a part of larger scholarly discussion on constructing local fiqh (al-fiqh al-mahalli) for Muslims. For such fiqh to evolve, a broader understanding of multifaceted aspects of the local family institution, its current problems and concerns warrant serious academic researches and evidencebased analysis. Therefore, scholarly papers contained in this book will fulfil this need in several ways including: first, some studies outline the juristic framework for contextualizing local factors into the Islamic methodology of renewal and reform; second, other researches evaluate the existing family laws with the prime purpose of suggesting relevant legislative and policy recommendations; third, some other studies deliberate on enhancing financial and the economic wellbeing of the family by advocating the introduction of more family-oriented Shariahcompliant services and products; fourth, a few studies focus on the family health by proposing that the existing policies on vaccination and pre-marital HIV screening need further improvements; and lastly, one study calls for integrating more religiosity elements into policies on career-women to enable them to better cope with the double task of family commitments and job responsibilities.